PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR TEMA 4 SUB TEMA 3 PEMBELAJARAN 2 SISWA KELAS III SDK TANALODU BAJAWA - Angela Bhebhe Watu; Andriyani A. Dua Lehan; Martha Khristina Kota (Journal of Character and ELementary Education, 2022)
The purpose of this study was to determine the effect of the Problem Based Learning model on the learning outcomes of Theme 4 Sub Theme 3 Learning 2 third-grade students of SDK Tanalodu Bajawa. The type of research used in this research is quantitative research with a Quasi-Experimental Design approach, namely Pretest-Posttest Nonequivalent Control Group Design. The population and samples used in this study were all third-grade students consisting of 38 students (19 students in the control class and 19 students in the experimental class). The data collection technique used in this study is the test technique. Based on the results of data analysis conducted using the independent sample t-test with SPSS version 16.0, it shows that the sig value (2-tailed) is 0.002 <0.05 with a significance level = 0.05 (5%), then Ha is accepted and H0 is rejected with the conclusion that there is a significant effect of the Problem Based Learning Model on Learning Outcomes of Theme 4 Sub Theme 3 Learning 2 Third Grade Students of SDK Tanalodu Bajawa.